ANALISIS EKONOMI USAHA PERIKANAN DOGOL DI DESA MUARA TELAKE KECAMATAN LONG KALI KABUPATEN PASER - salman man; Bambang Indratno Gunawan; Said Abdusysyahid (2339-1324, 2024)
Salman, 2022. Economic Analysis of Dogol Fishery Business in Muara Telake Village, Long Kali District, Paser Regency. Under the guidance of Bambang Indratno Gunawan. and Said AbdusysyahidPaser Regency, especially in Muara Telake Village, which is located in a coastal area which has enormous potential to support fishing activities. The purpose of this research is to analyze the profits of the dogol fishery business in Muara Telake Village, Longkali District, Paser Regency. Sampling using the census method. With the number of respondents as many as 30 people, the data analysis method uses business cost analysis, revenue analysis and profit analysis. According to the results of the analysis of the average operating costs incurred Rp.10.375,000/per month/respondent, the average revenue is Rp.16,800,000/per month/respondent and an average profit of Rp.6.425,000/permonth/respondent.